Foreword - Avetisyan, Pavel (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
About 150 years have passed since the first attempts of archaeological research in Armenia. During this period of Armenian archaeology much time had gone to the formation of theoretical and practical grounds and today we can say with confidence that a unique archaeological school had come into existence, which has established firm contacts with various similar centers throughout the world.